Investigation of Power Quality Improvement in Super Lift Luo Converter - J Gnanavadivel; N Senthil Kumar; C.N Naga Priya; K.S Krishna Veni (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper presents the improved single phase AC-DC super lift Luo converter for enhancing quality of power by mitigating the issues. The proposed converter is used for output voltage control, power factor improvement and reduced source current harmonics at supply side. The main intention of this work is to design appropriate closed loop controllers for this AC-DC super lift Luo converter to achieve  unity power factor in the source end. The designed control system comprises of two control loops, voltage control in outer loop and the current controller is devised in the inner loop. Fuzzy controller is used for current controller whereas PI controller as voltage controller. In the MATLAB/SIMULINK platform, simulation of the proposed AC-DC super lift Luo converter is done. It is clear from the simulation results that PI integrated fuzzy controller for voltage and control is proven to be better than classical PI with hysteresis controllers. The proposed system is able to achieve high input power factor along with supply current harmonic distortions of less than 5%.